2002
DOI: 10.1002/ajh.10154
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac abnormalities in children with sickle cell anemia

Abstract: Sickle cell anemia (SCA) results in chronic volume overload of the heart due to hemodilution. Previous echocardiographic studies of cardiac function in children with SCA have not accounted for these abnormal loading conditions. The objectives of this study were to (1) determine how the degree of anemia and transfusion status relate to cardiac findings and (2) evaluate cardiac function using load-independent parameters of function. We evaluated 77 patients with SCA, ages 2 to 22 years (mean ± SD = 11.7 ± 4.7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
2
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 38 publications
6
60
2
7
Order By: Relevance
“…Researchers have shown some degree of physiological cardiovascular adaptation in SCA patients, including elevations in heart rate and declines in cardiac output, primarily results from the associated chronic hemolytic anemia (Lester et al 1990, Batra et al 2002. Furthermore, Weiskopf et al reported linear increases in heart rates in healthy unmedicated human subjects as a result of acute isovolemic anemia (Weiskopf et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown some degree of physiological cardiovascular adaptation in SCA patients, including elevations in heart rate and declines in cardiac output, primarily results from the associated chronic hemolytic anemia (Lester et al 1990, Batra et al 2002. Furthermore, Weiskopf et al reported linear increases in heart rates in healthy unmedicated human subjects as a result of acute isovolemic anemia (Weiskopf et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although acute atherosclerosis-related myocardial infarctions are rare in SCA patients, diverse cardiovascular anomalies-including heart murmur, cardiomegaly, biventricular hypertrophy and abnormalities in the cardiac conducting system-which sometimes correlate to sudden death in SCA patients, have been described by multiple researchers (James et al 1994, Assanasen et al 2003, Norris et al 1991, Pavlu et al 2007, Manci et al 2003, Batra et al 2002. Transient cardiac dysfunction and myocardial ischemia have also been reported during sickle cell crisis (Norris et al 1991, Deymann andGoertz 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An increased prevalence of asthma was reported in one study of SCD children (5), but other studies have indicated a similar incidence to that of non-SCD populations (6,7). Another explanation for the airways obstruction in SCD is the hyperdynamic pulmonary circulation due to a raised cardiac output resulting from chronic anemia (8). In children with SCD, we have demonstrated that pulmonary capillary blood volume is increased compared to matched controls and correlated with airflow obstruction (9).…”
mentioning
confidence: 62%
“…In patients with liver cirrhosis, the enhanced NO output was shown to be of alveolar and not airway origin (17). Whether the hyperdynamic circulation in SCD patients (8) influences their F eNO levels has not been investigated.…”
mentioning
confidence: 99%
“…[8] Batra et al found systolic function and contractility to be preserved in their study. [25] Taksande A et al in their prospective controlled study found that left ventricular contraction was good and systolic function was normal in study population. [26] …”
Section: Systolic Function In Sickle Cell Anemiamentioning
confidence: 99%